The Positivity Scale: Evaluation of the Psychometric Properties of the Serbian Version - Žuljević, Dragan; Petrović, Vesna; Knežević, Zorica (Psihološka istraživanja, 2018)
The Positivity Scale (PS) (Caprara et al., 2012a) is an instrument which measures positivity formulated as the basic disposition for the assessment of oneself, life and the future in a positive way. The popularity of the scale and its wide use in different cultural contexts is based on the structural invariance of its translations in different languages. The aim of this paper was to test the basic psychometric properties of the PS on the sample of Serbian adults. The research included two studies. The aims of Study 1, conducted on the sample of 508 respondents, were to test the internal consistency and latent structure of the scale using exploratory factor analysis. The aims of Study 2, conducted on an independent sample of 1010 respondents, were to additionally test construct validity of the scale using confirmatory factor analysis, as well as to test convergent validity of the scale. The exploratory factor analysis results suggested a potential abbreviation from the initial eight items to six items. Concurrent validity was verified by adequate correlations with the measures of optimism (LOT-R; Scheier, Carver, & Bridges, 1994), self-efficiency (GSES; Schwarzer& Jerusalem, 1995)and self-respect (RSES; Rosenberg, 1965), and adequate correlations with the depression measures (CES-D; Radloff, 1977)and satisfaction with life (SWLS; Diener, Emmons, Larsen, & Griffin, 1985). It can be concluded that the PS translation is a reliable and valid instrument for the assessment of positivity. However, the peculiarities of our sample suggest that future research should additionally test structural validity of the PS and analyse in more detail specific manifestations of the positivity construct in our population.
Keywords: factor analysis; psychometrics; Serbia; Positivity Scale